Knowledge, Attitudes, and Experiences of Adolescents on Disaster Preparedness in an Area with a High Disaster Risk Index - Prastyawati, Irine Yunila; Djoar, Raditya Kurniawan; Anggarani, Anastasia Putu Martha; Pinto, Aurea da Piedade (TDMRC, Universitas Syiah Kuala, 2024)
Studies evaluating teenage knowledge, attitudes, experiences, and readiness for disasters in high-risk areas are scarce, nevertheless. Determine the elements that influence teenage readiness for disasters in an area with a high disaster risk index. 170 high school students in their eleventh grade participated in an anonymous online survey as part of a cross-sectional study design. Purposive sampling was used to choose the respondents. Surabaya was chosen as the study site because it has a high disaster risk index. The partial impact of knowledge, attitudes, experience, and disaster preparedness was determined using the t-test, and the R-Square. It was found that attitudes and prior experience regarding disaster preparedness had a partial influence. The partial test between experience and disaster preparedness and the partial test between attitude and disaster preparedness showed that teenagers in an area with a high disaster risk index had different attitudes and experiences when it came to being prepared for disasters. According to the report, high schools and the government should encourage regular training so that teenagers can get positive attitudes and more experience with disaster preparedness